Typification of plant names referable to Phagnalon (Compositae) with some taxonomic notes - Montes-Moreno, Noemí; Garcia-Jacas, Núria; Nualart, Neus; Susanna, Alfonso; Sáez, Llorenç (Phytotaxa, 2018)
As part of a taxonomic study in Gnaphalieae and other Compositae, 45 new lectotypes, 1 epitype and 3 neotypes are designated for names in Phagnalon, Conyza and Pluchea. Typifications are discussed, together with taxonomic notes on these taxa and references to previous lectotypifications. The accepted names for which we propose lectotypifications are: Ph. acuminatum, Ph. barbeyanum, Ph. bicolor, Ph. ×caroli, Ph. carolipaui, Ph. harazianum, Ph. kotschyi, Ph. ×intermedium, Ph. latifolium, Ph. melanoleucum, Ph. phagnaloides, Ph. persicum, Ph. pygmaeum, Ph. quartinianum, Ph. rupestre subsp. rupestre, Ph. rupestre subsp. graecum, Ph. saxatile, Ph. schweinfurthii, Ph. sinaicum, Ph. stenolepis, Ph. ×telonense and Ph. viridifolium.